2019
DOI: 10.4236/ajibm.2019.99117
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Coherence: A Novel Determinant of Open Innovation Performance

Abstract: Despite its popularity as a strategy to accelerate innovations there is evidence that open innovation does not always increase innovation performance. Extant literature provides inconsistent and inconclusive arguments in respect of the relationship between open innovation practices and innovation performance. Existing theories mostly have an internal focus and fall short of explaining why some firms succeed in open innovation initiatives and why others fail. Open innovation is about knowledge flows. We argue t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Sequential coherence refers to the reciprocal result of the pushing effects induced by individuals of a teaching firm and the pulling effects induced by individuals of a learning firm that enables knowledge to flow across the boundaries of firms (Yapa et al, 2019a). Sequential coherence can be measured by the ability and willingness to teach by the individuals in the teacher firm and the ability and readiness to learn by the individuals in the student firm.…”
Section: Sequential Coherencementioning
confidence: 99%
“…Sequential coherence refers to the reciprocal result of the pushing effects induced by individuals of a teaching firm and the pulling effects induced by individuals of a learning firm that enables knowledge to flow across the boundaries of firms (Yapa et al, 2019a). Sequential coherence can be measured by the ability and willingness to teach by the individuals in the teacher firm and the ability and readiness to learn by the individuals in the student firm.…”
Section: Sequential Coherencementioning
confidence: 99%
“…The qualitative inquiry we made revealed that sequential coherence that facilitates the knowledge transfer at boundary level influence innovation performance in open innovation initiatives. Sequential coherence refers to the reciprocal result of the pushing effects induced by individuals of a teaching firm and the pulling effects induced by individuals of a learning firm that enables knowledge to flow across the boundaries of firms (Yapa et al, 2019). Sequential coherence is measured through the push and the pull effects by willingness and ability of the participants of teacher firm and the preparedness and ability of the participants from the student firm respectively (Yapa et al, 2020).…”
Section: Sequential Coherencementioning
confidence: 99%